Pengembangan Media Hologram pada Materi PAI Thoharoh Wudhu di PKBM Generasi Juara Semarang - Falillah Risti Nur Maghfiroh; Sony Zulfikasari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to develop a hologram learning media for Islamic Religious Education (PAI) on the topic of Thaharah (Wudhu) for learners in the Package C Program at PKBM Generasi Juara Semarang and to determine the feasibility level of the developed media. The study was motivated by the limited use of instructional media, highlighting the need for innovative learning tools capable of presenting wudhu practice materials in a more engaging and understandable manner. This research employed a Research and Development (R&D) method by adapting the 4D development model (Define, Design, Develop, Disseminate) up to the Develop stage. The research procedures included needs analysis, media design, product development, expert validation, and product revision. The developed media consisted of a hologram-based learning tool on the topic of Thaharah (Wudhu), displayed using a smartphone and a hologram box. Research data were collected through validation questionnaires completed by material experts and media experts. The results showed that the hologram media obtained a feasibility score of 85.0% from the material expert, categorized as Very Good/Feasible, and 99.2% from the media expert, categorized as Very Valid/Highly Feasible. Based on these validation results, the hologram learning media was declared feasible for use in Islamic Religious Education learning on the topic of Thaharah (Wudhu).